Strength training for people with multiple sclerosis and the current recommendations - Gooch, Helen (Br J Neurosci Nurs, 2021)
Recent guidelines recommend strength and conditioning training for patients with multiple sclerosis (MS). This article evaluates and summarises four systematic reviews examining strength training for people with MS and examines if these reviews substantiate these current guidelines.